Tracking the phage trends: A comprehensive review of applications in therapy and food production - Jaglan, Anu Bala; Anand, Taruna; Verma, Ravikant; Vashisth, Medhavi; Virmani, Nitin; Bera, B. C.; Vaid, R. K.; Tripathi, B. N. (Frontiers in Microbiology, 2022)
In the present scenario, the challenge of emerging antimicrobial resistance is affecting human health globally. The increasing incidences of multidrug-resistant infections have become harder to treat, causing high morbidity, and mortality, and are posing extensive financial loss. Limited discovery of new antibiotic molecules has further complicated the situation and has forced researchers to think and explore alternatives to antibiotics. This has led to the resurgence of the bacteriophages as an effectivealternative as they have a proven history in the Eastern world where lytic bacteriophages have been used since their first implementation over a century ago. To help researchers and clinicians towards strengthening bacteriophages as a more effective, safe, and economical therapeutic alternative, the present review provides an elaborate narrative about the important aspects of bacteriophages. It abridges the prerequisite essential requirements of phage therapy, the role of phage biobank, and the details of immune responses reported while using bacteriophages in the clinical trials / compassionate grounds by examining the up-to-date case reportsand their effects on the human gut microbiome. This review also discusses the potential of bacteriophages as a biocontrol agent against food-borne diseases in the food industry and aquaculture, in addition to clinical therapy. It finishes with a discussion of the major challenges, as well as phage therapy and phage-mediated biocontrol's future prospects.